Biofabrication of Gelatin Tissue Scaffolds with Uniform Pore Size via Microbubble Assembly. Issue 11 (8th November 2019) - Bayram, Cem; Jiang, Xinyue; Gultekinoglu, Merve; Ozturk, Sukru; Ulubayram, Kezban; Edirisinghe, Mohan
Abstract : Front Cover : Achieving a uniform porosity is crucial in tissue engineering scaffold design. In article number 1900394 by Mohan Edirisinghe and co‐workers, a method for fabricating porogen‐free gelatin scaffolds with a narrow pore size distribution using simple T‐junction microfluidics is described. It offers an economical approach for the preparation of gelatin scaffolds with homogenous porosity which can be utilized in diverse healthcare engineering applications, especially in pore size dependent scenarios.